The logic of CPTED for public space or the social potential of physical security - Gooren, Juul (Crime, law and social change, 2023)
In order to address crime, it is popular to use situational crime prevention with its focus on immediate opportunities for offending. If targets become less suitable and if capable guardians are present, then crime is less likely to take place in the here and the now. This logic often translates into placing greater distance between targets and motivated offenders. For industrial security, this comes down to deterring, denying, detecting and delaying ("the four D’s") any type of intrusion in order to protect assets. For public security, this comes down to surveillance, access control, territoriality, maintenance and activity support in order to prevent crime. While considering public security, this article will reflect on the possibilities of Crime Prevention Through Environmental Design (CPTED).